Delito de robo con fuerza en las personas y su incidencia en la tipicidad penal - Toapanta Cacuango, Estefanía Mishel (2025)
n principle, the objective of this research is to analyze the crime of stealing with force againts people and its incident in the criminal typicality, in the community of Chaupiloma, Pedro Moncayo canton, during the year 2024, which constitutes the basis of justification of the present investigation and whose contribution is important to carry out this study, several research approaches were also employed; for the content analysis, a documentary guide was used to address the topics, and descriptive tools to comprehend the object of study. In the interviews, a questionnaire with nine open questions was employed, the investigation was exploratory, descriptive, analytic and explanatory. The survey revealed that 95% of the surveyed know exhaustively the legal elements that set up the crime of stealing with force against people, while 5% are not sure. In effect, the multicomponent judges, Criminal Court, Prosecutor’s Office and Political Headquarters of Pedro Moncayo canton, in the accomplishment of their functions and competencies according to the legal system, work in coordination with the police to guarantee compliance with the rules, preserve security, tranquility, taking preventing measures in the crime of stealing with force against people commitment, specially in the community of Chaupiloma, however, although there are challenges such as lack of clarity in the rules, therefore, their work is essential to maintain security and order, in addition, to generate a doctrinal, judisprudential and positive opinion contribution.